Responsible Leadership Competencies in leaders around the world: Assessing stakeholder engagement, ethics and values, systems thinking and innovation competencies in leaders around the world. (7th December 2021) - Muff, Katrin; Delacoste, Coralie; Dyllick, Thomas
Abstract: This article builds on the competency assessment of responsible leadership (CARL) developed by Muff et al. (Corporate Social Responsibility and Environmental Management Journal, 2020, 27, 2254–2274) and assesses the data collected from a sample of 9'566 participants across 122 countries in the timeframe. The analysis reveals interesting, sometimes counter‐intuitive, insights that advance current thinking on the topic of responsible leadership (RL). As such "self‐awareness" emerges as the central element in RL. There is evidence suggesting that higher education leads to a better RL performance. Interestingly, the study highlights that participants in the African region outperform other participants. In addition, a sustainability affinity does not lead to a higher RL score, and CEOs from sustainability‐conscious organizations do not perform better than their demographic peers. The data suggests that executives do not increase their RL performance after a leadership development course, while undergraduate students do. The paper explores some answers while acknowledging that more research is needed to understand how these insights inform leadership education.